The Christian Faith : A Creedal Account - Schwarz, Hans, 1939- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2014)
This reader-friendly primer offers a concise yet thorough overview of the Christian faith. Hans Schwarz, one of the major Lutheran theologians of the last half-century, covers the Christian faith from creation to the final fulfillment of life. He gives his account of the major points of Christian doctrine, always moving from the biblical text to the unfolding of the faith through the centuries to contemporary significance. This brief systematic theology will appeal to professors, students, pastors, and educated lay readers who want a quick but profound and biblically grounded overview of the Christian faith
Introduction: Luther's central insights -- Presuppositions for the faith -- Theology -- Revelation -- Scripture -- God the creator -- God -- Creation -- Humanity -- Sin -- Christ the redeemer -- Jesus of Nazareth -- Jesus as the Christ -- The Holy Spirit as God's efficacious power -- The Holy Spirit -- The Church -- The means of grace -- The Christian hope
Includes index
Includes bibliographical references and index
Keywords: Christian Theology and Doctrines; Lutheran Church -- Creeds; Lutheran Church -- Doctrines; Christian Theology - Beginning and History; Christian Faith and Creeds